Physical and electrical properties of bismuth strontium oxide - based solid solutions - Mohd Noor, Rohayu (2019)
Bismuth oxide systems exhibit high oxide ion conductivity and have been proposed as good electrolyte materials. However, due to their instability under conditions of low oxygen partial pressures there has been difficulty in developing these materials and thus, strontium is introduced in order to overcome this problem. The bismuth strontium oxide (Bi2-2xSrxO3-2x) where 0.1 ≤ x≤ 0.8 is synthesized via conventional solid state method at 800°C for 24-48 hours. X-ray diffraction studies revealed that the single phase hexagonal structure with space group of R-3m and lattice parameter of a=b≠c is attained in composition of 0.1 ≤ x≤ 0.4. Mixed phases were obtained for the composition of 0.5 ≤ x≤ 0.8 and therefore, it can be concluded that the solid solution limit for this material is in the composition of 0.1 ≤ x≤ 0.4. The electrical properties were studied using AC impedance in the frequency range of 0.1 Hz – 1 MHz at temperature of 25-800°C. At temperature 200-400°C, Bi2-2xSrxO3-2x solid solutions were having an oxide ionic conduction with conductivity ~10-6 -10-1 Scm-1 while the activation energies, Ea were in the range of 0.76-1.12 eV. Chemical doping using divalent cations were carried out on the Sr2+ site with selected dopants i.e. manesium oxide (MgO), calcium oxide (CaO), barium oxide (BaO) and nickel oxide (NiO) in order to modify and enhance the electrical properties of the material and all dopants were introduced into Bi1.2Sr0.4O2.2. The divalent dopants are introduced at Sr2+ site because of its comparable ionic radius to Sr2+. The single phase pure of these samples were determine by using the X-ray diffraction method (XRD). The solid solution limit for Mg-doped (Bi1.2Sr0.4-xMgxO2.2) is 0.00 ≤ x≤ 0.10 meanwhile, solid solution limit for Ca-doped (Bi1.2Sr0.4-xCaxO2.2) is 0.00 ≤ x≤ 0.08. The solid solution limit for Ba-doped (Bi1.2Sr0.4-xBaxO2.2) is in the range of 0.00 ≤ x ≤ 0.06 and as for the Ni-doped (Bi1.2Sr0.4-xNixO2.2) the solid solution limit is 0.00 ≤ x ≤ 0.10. All of these doped materials are in hexagonal structure with space group of R-3m. At temperature of 200-400°C the ionic conductivity for Bi1.2Sr0.4-xMgxO2.2 solid solutions are 10-6-10-1 Scm-1 with activation energy in the range of 0.93-0.97 eV. The Bi1.2Sr0.3Mg0.1O2.2 has the highest conductivity of 1.23x10-1 Scm-1 at 400°C. An increase in conductivity was observed as the composition of Ca-doped increased; at temperature of 200-400°C is in the range of 10-6-10-2 Scm-1 with activation energy in the range of 0.96-1.14 eV. The Bi1.2Sr0.32Ca0.08O2.2 has the highest conductivity at 400°C which is 5.62x10-2 Scm-1and Ea is 1.14 eV. The conductivity decreased as the amount of Ba2+ increases. The ionic conductivity at temperature of 200-400°C is 10-6-10-2 Scm-1 and Ea is 0.89-1.10 eV. The Bi1.2Sr0.36Ba0.04O2.2 is having high conductivity of 5.33 x 10-2 Scm-1 at 400°C as compared to the Bi1.2Sr0.4O2.2. The ionic conductivity of Ni-doped at temperature of 200-400°C is 10-6-10-2 Scm-1 with the activation energy of 0.69-1.07 eV. The Bi1.2Sr0.38Ni0.02O2.2 has the highest conductivity of 2.88 x 10-2 Scm-1 at 400°C. The atomic percent of elements present in all samples were confirmed by using the energy dispersive X-ray spectroscopy (EDX). Surface morphology of these samples was viewed using the scanning electron microscopy (SEM).